2022
DOI: 10.1007/s10071-022-01696-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of mirror self-recognition in three corvid species

Abstract: Mirror self-recognition (MSR) assessed by the Mark Test has been the staple test for the study of animal self-awareness. When tested in this paradigm, corvid species return discrepant results, with only the Eurasian magpies and the Indian house crow successfully passing the test so far, whereas multiple other corvid species fail. The lack of replicability of these positive results and the large divergence in applied methodologies calls into question whether the observed differences are in fact phylogenetic or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 119 publications
0
8
0
Order By: Relevance
“…This is quite interesting because these corvid species all failed to pass the classic mark-test and, more importantly, the behaviors often considered as indicators of the ability to pass the mark-test (exploratory behavior, contingent behavior and self-exploration) were limited both in the occurrences displayed, as well as in the number of individuals displaying them ( Brecht, Müller & Nieder, 2020 ; Vanhooland, Bugnyar & Massen, 2020 ; Wang et al, 2020 ). Our results indicate that neophobia can posit a challenge for the jays, and most likely to other corvids as well, to approach and explore the mirror, appreciate its reflective property, and use it to explore parts of their body otherwise not visible ( Vanhooland et al, 2023 ).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…This is quite interesting because these corvid species all failed to pass the classic mark-test and, more importantly, the behaviors often considered as indicators of the ability to pass the mark-test (exploratory behavior, contingent behavior and self-exploration) were limited both in the occurrences displayed, as well as in the number of individuals displaying them ( Brecht, Müller & Nieder, 2020 ; Vanhooland, Bugnyar & Massen, 2020 ; Wang et al, 2020 ). Our results indicate that neophobia can posit a challenge for the jays, and most likely to other corvids as well, to approach and explore the mirror, appreciate its reflective property, and use it to explore parts of their body otherwise not visible ( Vanhooland et al, 2023 ).…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, the time in direct view of the mirror was definitely less compared to when birds were tested in a more confined testing compartment and forced to face the mirror. The effective time in front of the mirror has also been proposed to explain the overall delayed occurrences of contingent behavior in ravens or a lack of interest towards the mirror in azure-winged magpies ( Vanhooland, Bugnyar & Massen, 2020 ; Vanhooland et al, 2023 ). On the other hand, some suggestive evidence of MSR has been proposed to have been found in mirror-naïve Clark’s nutcrackers presented with a social caching task in a small compartment (in which they were in view of a mirror most or all of the time; Clary & Kelly, 2016 ), as well as in another mirror-related cache-protection study involving California scrub-jays without previous mirror exposure ( Dally, Emery & Clayton, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among nonhuman mammals, it has been consistently seen in individual chimpanzees, orangutans, and dolphins, and in Asian elephants, gorillas, and gibbons mirror‐guided self‐recognition was seen in some studies and individuals but not others (Emery & Clayton, 2004b; Prior et al., 2008; Ristau, 2013). By contrast, among avian species thought to parallel apes in their intelligence, common ravens, azure‐winged magpies, carrion crows, jungle crows, and African grey parrots have not shown mirror‐guided self‐recognition (Emery & Clayton, 2004b; Vanhooland et al., 2022; Wang et al., 2020), although such self‐recognition was reported in Indian crows (Parishar et al., 2021) and in three of five Eurasian magpies (a corvid) tested (Prior et al., 2008), but not in another study of a larger magpie cohort (Soler et al., 2020). Moreover, although crows mimic chimpanzees in tool use, some authors have shown that chimpanzees can be taught to communicate using human sign language (Gardner & Gardner, 1980), but there is no such evidence for language use by corvids, suggesting that while corvids may cognitively match chimpanzees in some regards, they do not do so in all regards.…”
Section: Assumptions For Evaluating the Possibility Of Evolution Of A...mentioning
confidence: 99%